Bacterial Interactions with Dental and Medical Materials - Melo, Mary Anne (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The interaction of bacteria with biomaterials' surfaces has critical clinical implications on the development and progression of biofilm-related diseases. In this book "Bacterial Interactions with Dental and Medical Materials", encouraging findings on tissue-contacting biomaterials to control biofilms, enhanced understanding of key mechanisms, and clinical perspectives are discussed toward improving healthcare.